An interview with Kevin Dowling, CEO of KAARTA (GEOmedia, 2021)
The name ‘Kaarta' is a phonetic reference to cartography, the science or practice of map making, and all things cartographic. Kaarta, the company, is all about mapping and localization.The name – with the extra a added for effect – captures the company'spioneering take on mapping to produce 3D models in real time.The name is not about the technique we use, it's about the problems we solve.